Implementação e análise de protocolos de roteamento para redes mesh sem fio LoRa - Medeiros, Douglas de Farias (2021)
In a world getting more and more connections, the growth of the number of devices sharing autonomously data with each other has been evident. The connectivity of all these devices is directly related to the concepts of Internet of Things and Smart Cities, which has gaining much attention currently. Therefore, as the number of connected devices and their applications grows, the amount of data shared by these devices also increases considerably. Thus, in order to be able to send data from one device to another passing through intermediate devices, it is necessary to define the path to the data to be sent, characterizing the concept of routing. In this context, this work aims to implement and analyze different routing protocols for application in Smart Cities. In addition, a tool for calculating the distance range of nodes using the Egli propagation model was also developed and integrated on Cupcarbon simulator. Furthermore, this work also showed a proposal for a transmission power adjustment algorithm with the objective of saving energy at the network nodes. The LoRa wireless communication technology and a scenario of simulation composed by a mesh network topology distributed along avenues in the city of João Pessoa - PB were considered. The evaluation criteria were the packet delivery rate, the average end-to-end delay, the average jitter and throughput. The energy consumption profiles of each network node were also obtained according to each protocol. The results showed that the DSR protocol was the most appropriate option among those implemented to be used with the transmission power adjustment algorithm proposed in this work. This algorithm provided an energy saving of 11.32% compared to the original DSR. On the other hand, the AODV protocol achieved better general performance and presented the second highest energy consumption. Finally, the DVR protocol was the one that consumed the most energy and performed better in terms of latency, but presented high packet loss. In the end, experimental tests were performed using the DSR protocol and an application on The Things Network (TTN) server.